Antecedents and Consequences of Participation in a National Lesbian, Gay, Bisexual, and Transgender (LGBT) Workplace Conference - Julie Gedro (Adult Education Research Conference, 2007)
This qualitative study examined participant motivation and outcomes of a national LGBT workplace conference. The conference provides educational workshops on a variety of LGBT related workplace issues, designed to provide information, education, business case strategies and personal empowerment.